The influence of work-life balance on job satisfaction and intention to stay of Chinese post-90s employees - Yu, Qilu (2020)
Employees nowadays pay more attention to work-life balance, especially Chinese post-90s employees. They account for a large proportion of the labour market and have different characteristics compared with other generations. Thus, it is necessary to investigate the importance of work-life balance for post-90s employees in China, which may help managers create better policies to manage post-90s employees. This study uses quantitative method with the form of survey, distributing and collecting questionnaires online. This study also analyses data by SPSS to verify hypotheses and compares the results with previous research. Finally, this study found that work-life balance has a positive effect on job satisfaction and intention to stay of Chinese post-90s employees. In addition, gender and the number of jobs affect the degree of the influence of work-life balance on job satisfaction and intention to stay, while there is no significant correlation between marital status and this influence.